Portada principal del Diario Extra y las ventas en la Parroquia Viva Alfaro, ciudad de Quevedo, año 2019 - Villegas Morales, Esther Elizabeth (2020)
The written press plays a fundamental role in the life of modern societies, because it shows events, conflicts, trajectory, political life, sports, social events, among others. The Ecuadorian press from its origin as a means of communication focused on the voice of the people, the content of the press in general is characterized by its political, literary and advertising content. The front page of the newspapers is your cover letter, where the reading public is in charge of choosing the newspaper that you like the most or attracts your attention. The Extra Newspaper written press whose first edition was published in the year 1974. For several years it was characterized by having a serious line of news, but in the year 1988 its managers decided to lean on issues of abuse and violence, already in the year 2000 decided to incorporate into its sections the Sexy Monday, a space created of a sexist type and directed towards the male market. The purpose of this research is to determine the impact of the main front page of the extra newspaper and its impact on the level of sales in the Parroquia Viva Alfaro. For the collection of information, research sources and techniques were used, the first being collected through bibliographic information from books, texts and scientific publications, while the survey technique allowed to know the opinion that readers have regarding this newspaper